Corrosion of Al 7075 alloy during the production of aeronautic components: Influence of process parameters at the deburring stage. Issue 12 (16th May 2012) - Faria, M. I. S. T.; Robin, A.; Prisco, L. P.; Puccini, M. C.; Gonçalves, D. C.; Lourenço, J. C.
Abstract Aluminum alloys of the 7XXX series are widely used in aircraft applications. During the manufacturing of aeronautic components, the parts pass through four production phases (milling/drilling, deburring/adjustment, non‐destructive testing, and surface treatment) and come into contact with several kinds of fluids such as degreasing and cleaning solutions, which can lead to the occurence of surface defects due to localized corrosion, then requiring reworking or scrapping. The present study aimed at studying the influence of process parameters in the deburring/adjustment stage on the development of surface defects in 7075 alloy parts. The methodology consisted of design of experiments, immersion and drying tests, and surface analysis for quantification of corrosion damage. The results showed that the degreasing bath concentration and temperature, the immersion time of the aluminum parts in the degreasing solution, and the use of solvent pre‐cleaning had no significant influence on the quantity of surface defects. Therefore, these factors do not need to be rigorously controlled in the process. Clean washing water must be preferred and the parts must be dried in the stove at 110 °C in order to ensure a surface free of defects. The immersion and electrochemical tests showed that the occurrence of surface defects is lower in aged degreasing solution than in recently prepared solution.